THE PRACTICE OF RHYTHMIC GYMNASTICS: THE CASE OF GRÊMIO NÁUTICO UNIÃO CLUB OF PORTO ALEGRE/RIO GRANDE DO SUL - Patrícia Silveira Fontana; Ester Liberato Pereira; Janice Zarpellon Mazo (Universidade Estadual do Oeste do Paraná, 2013)
The present study aims to reconstruct, through oral and documental sources, the process of introducing the practice of Rhythmic Gymnastics in Grmio Nutico Unio (GNU) Club, which occurred in the late 1970s to the participation of their athletes and coaches in the Pan American Games in 1999 in Winnipeg, Canada. The documental analysis and interviews revealed that the GNU has contributed to the recognition of the state of Rio Grande do Sul as one of the poles of RG in Brazil.